The Impulsive Coupled Langevin ψ-Caputo Fractional Problem with Slit-Strip-Generalized-Type Boundary Conditions - Haroon Niaz Ali Khan; Akbar Zada; Ioan-Lucian Popa; Sana Ben Moussa (Fractal and Fractional, 2023)
In this paper, the existence of a unique solution is established for a coupled system of Langevin fractional problems of <semantics>ψ</semantics>-Caputo fractional derivatives with generalized slit-strip-type integral boundary conditions and impulses using the Banach contraction principle. We also find at least one solution to the aforementioned system using some assumptions and Schaefer’s fixed point theorem. After that, Ulam–Hyers stability is discussed. Finally, to provide additional support for the main results, pertinent examples are presented.